Visualizing the strategic landscape of arbitrary games. (July 2018) - Osborn, Joseph Carter; Samuel, Benjamin; Mateas, Michael
We present Gamalyzer, a game-independent and efficient visualization of sets of play traces. Unlike previous work on game-independent visualization, we focus on sequences of game actions as opposed to sequences of game states. Action sequences directly represent players' strategic decisions. Moreover, since game actions may already be recorded as part of games' telemetry and metrics, Gamalyzer is easier to integrate into existing analysis toolchains than state-sequence-based visualizations. Gamalyzer displays each play trace as a vertical line, with symbols along the line indicating game events. Similar play traces (according to the Gamalyzer metric, a specialization of edit distance) are arranged together along the horizontal axis, and as traces become more and less similar to each other over time, they bend towards and away from each other. The Gamalyzer metric is also used to present only the most interestingly different traces in the visualization, with the rest grouped together under their most similar cousins. We position Gamalyzer as an ideal trace filtering and selection tool to be used in concert with a state-centric (and possibly game-specific) visualization for context. This article also provides a detailed account of the Gamalyzer metric and new advice for defining game action schema to maximize the benefits obtained from the tool, along with two detailed case studies of the Gamalyzer visualization in practice.